IMPACT OF COAGULANTS ON THE TSS SEPARATION PERFORMANCE IN CLEAN WATER PRODUCTION : AN EXPERIMENTAL FINDINGS - M. Shahidul, Islam; Michael, A. B.; Rubiyah, Baini; Adzlan, A. F.; Hishammudin Afifi, Huspi (Publications International Lahore, Pakistan, 2023)
This paper reports an experiment conducted with a feed water contained low level total suspended solid (TSS≤ 10 mgL-1 ). This research aims to investigate a problem to justify whether coagulants is required to filter that feed water to produce required clean water (TSS≤ 1.0 mgL-1 ). This research has been conducted with combined use of Multi Media Water Filter (MWF) and Micro Filter (MF). The water filtration rate of this experiment was 20.0 m3(d) -1 . The TSS in product water (PW) was 0.735 mgL-1 when the plant was operated with coagulants. When the plant operated without coagulants the TSS content in PW was 0.876 mgL-1 . Two sets of experimental data were analysed and tested with paired-samples t-test at a 95% confidence level. The result demonstrated that the P-value was more than 0.05 (>0.05) when compared to the mean difference between the data sets. This finding indicates that the TSS content in PW of these two processes is nearly equal, and there is no significant difference between the two processes. This finding could be a reference to the water industry, engineering professionals and policy implementation agencies relating to the use of coagulants in the WF process. This study concludes that coagulants are not required in the WF process when feed water contains TSS less than 10 mgL-1 and the MWF can significantly remove TSS from feed water to produce the required clean water. This study recommends similar further research with various types of feed water to develop a standard model for the WF process to achieve SDG 6, SDG8, and SDG13.